Carbohydrate feeding during exercise - Jeukendrup, A. E. (European Journal of Sport Science, 2008)
Carbohydrate ingestion can improve endurance capacity and performance. Since the 1980s, research has focused on optimizing the delivery strategies of these carbohydrates. The optimal dose of carbohydrate is still subject to debate, but recent evidence suggests that there may be a dose-response effect as long as the carbohydrate ingested is also oxidized and does not result in gastrointestinal distress. Oxidation rates of a single type of carbohydrate do not exceed 60 g·h-1. However, when multiple transportable carbohydrates are ingested (i.e. glucose and fructose), these oxidation rates can be increased significantly (up to 105 g·h-1). To achieve these high oxidation rates, carbohydrate needs to be ingested at high rates and this has often been associated with poor fluid delivery as well as gastrointestinal distress. However, it has been suggested that using multiple transportable carbohydrates may enhance fluid delivery compared with a single carbohydrate and may cause relatively little gastrointestinal distress. More research is needed to investigate the practical applications of some of the recent findings discussed in this review.